(untitled) (Impetus, 2021)
This article comes from the results of qualitative research on the theoretical and practical elements developed by physical education teachers and students, in relation to ubiquitous learning and mobile learning. Taking into account the experiences associated with ICT and its uses in the classroom at the Inem Luis López de Mesa educational institution (Inem) and the Antonio Villavicencio Cooperative School (Antonio Villavicencio) in the city of Villavicencio, Meta. For this, it was taken into account to identify and analyze ubiquitous and mobile learning from teaching-learning, interpreting and comparing the discourses of students and teachers about these learnings in the physical education class in these institutions, using a case study comparative thinking about a contemporary phenomenon within a real life context. Yielding results how: the promotion of recursion, creativity and the incorporation of new elements, facilitating experiences and even innovation, professional and investigative updating, which increases the attractiveness of the learning-teaching processes and vice versa.